Kindred Spirits: Lajos Gulácsy and Oscar Wilde - Péteri, Éva (Hungarian Journal of English and American Studies, 2021)
Lajos Gulácsy (1882-1932), the acknowledged Hungarian painter of the early twentieth century, was a kindred spirit to Irish playwright and poet Oscar Wilde (1854-1900), sharing his love of beauty, his escapism, and his belief in the superiority of art over mundane reality. Gulácsy’s art cannot be easily described in relation to the artistic groups and tendencies of his age; however, the literary portion of his oeuvre reveals definite affinities and parallels with dominant artistic trends of the millennium. Gulácsy wrote a number of essays, short-stories and tales, and even a novel, Pauline Holseel (1910), which all give evidence to an aesthetic similar to that of Oscar Wilde. Pauline Holseel, in particular, shows close correspondences with Wilde’s novel, The Picture of Dorian Gray (1890). Besides displaying the typical features of the Künstlerroman of the late nineteenth, early twentieth century, such as the lack of a plot, artists as protagonists, or a heavy reliance on sensual experiences, they also share more particular parallels concerning structure and attitude to art. (ÉP)